Assessing the Impact of Point-of-Sale Beer Brand Ads Through Consumer Neuroscience Research - Lukić, Darko; Starčević, Slađana; Pitić, Goran (Naše gospodarstvo/Our economy, 2025)
This study employs EEG and eye-tracking to assess how brand equity, creative complexity, and spatial layout influence implicit consumer responses to point-of-sale (POS) beer advertisements. Through the theoretical lens of predictive coding and processing fluency, laboratory testing with Serbian beer consumers (N = 20) revealed that simpler designs yielded superior attention performance across TFD and TTFF (d up to 2.62), independent of brand strength. Spatial repositioning reduced packshot detection time by 0.89s (p<0.001, d=1.78) in horizontal versus vertical layouts. EEG showed no significant brand differences (valence d=0.07, p=0.765), offering a theoretical interpretation consistent with predictive coding, wherein expected stimuli elicit reduced neural activation, with brand strength operating solely through attentional pathways. Eye-tracking revealed strong brands’ automatic attentional capture of iconic elements (e.g., letter ’J’; TTFF=0.47s), theoretically reconciled via processing fluency as effortless decoding. We derive actionable POS benchmarks: packshot detection < 0.5s, slogan engagement > 1.0s, emotional valence > 5.0, cognitive load < 5.0. This advances GDPR/NDA-compliant methodology while offering practical guidelines grounded in neurocognitive theory.